2019
DOI: 10.1080/02791072.2019.1571258
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mental Health across Distinct Groups of Users of Psychedelics, MDMA, Psychostimulants, and Cannabis

Abstract: Differences in mental health (MH) of users of distinct psychoactive substances have been shown. Both substance use (SU) and MH in users is influenced by stressful life events. This study compared MH parameters in distinct groups of substance users and evaluated the impact of stress factors on these outcomes. Data stem from the longitudinal Swiss Cohort Study on Substance Use Risk Factors (C-SURF) involving 4,475 young adult men. Distinct groups were created for the past 12 months use of psychedelics, MDMA, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Contrary to amphetamine, classic psychedelics [i.e., serotonin 2A receptor agonists such as lysergic acid diethylamide (LSD), psilocybin, DMT, and mescaline] seem to present a relatively low potential for adverse effects on users and society compared to other substances (i.e., low physical and social harm potential and substance use disorder development) ( 10 ). For instance, a longitudinal study involving distinct groups of people in Switzerland using psychedelics, MDMA, psychostimulants, and cannabis found no differences in mental health between users of psychedelics and subjects who used no substances; however, people using other substances were associated with poorer mental health ( 11 ). Similarly, one large-scale population-based study found no significant associations between the use of psychedelics and any adverse mental health outcomes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to amphetamine, classic psychedelics [i.e., serotonin 2A receptor agonists such as lysergic acid diethylamide (LSD), psilocybin, DMT, and mescaline] seem to present a relatively low potential for adverse effects on users and society compared to other substances (i.e., low physical and social harm potential and substance use disorder development) ( 10 ). For instance, a longitudinal study involving distinct groups of people in Switzerland using psychedelics, MDMA, psychostimulants, and cannabis found no differences in mental health between users of psychedelics and subjects who used no substances; however, people using other substances were associated with poorer mental health ( 11 ). Similarly, one large-scale population-based study found no significant associations between the use of psychedelics and any adverse mental health outcomes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is predominantly seen as a safe drug in Western societies [ 8 ]. Life satisfaction and stress do not seem to predict the initiation, cessation, or severity of cannabis use in young adults [ 9 , 10 ]; however, research indicates a higher prevalence of various mental health symptoms in cannabis users, such as depression, anxiety [ 10 - 13 ], and attention deficit/hyperactivity disorder, with increased severity in certain populations such as those in the Czech Republic and France [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the positive long term therapeutic effects of psychedelics have been relatively well attended to since the resurgence of clinical psychedelic research ( Rougemont-Bücking et al, 2019 ), their role in intergroup dynamics is less understood. Psychedelics, serotonergic hallucinogens, induce an altered state of consciousness commonly framed as powerful modifications to perception and mood lasting several minutes to 24 hours, or even more, depending on what is consumed, how much, and the method of ingestion.…”
Section: Introductionmentioning
confidence: 99%